ANTIOXIDANTACTIVITYIN VITRO AND HEPATOPROTECTIVE EFFECTS IN VIVO OF COMPOUND LOBELIA - Cui, Xuejing; Gu, Xuezhu; Kang, Wenyi (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Chinese medicine has its own uniqueness, advantageous in the treatment of hepatic diseases, and they were widely used in the oxidation.At the same time, oxidation is one of the mechanism of protect liver. Materials and Methods: In the present study, the antioxidant activity in vitro of different extracts from Compound Lobelia were estimated respectively by the methods of measuring the [2,2′-azino-bis(3-ethylbenzothiazoline)-6-sulphonic acid] diamonium salt (ABTS) radical scavenging, ferric reducing antioxidant power (FRAP). The protective effects on carbon tetrachloride (CCl4)-induced acute liver injury in mice which was investigated by analyzing the result of biochemical parameters such as glutamic oxaloacetic transaminase (GOT) and glutamic pyruvic transaminase (GPT) in serum, superoxide dismutase (SOD) and malondialdehyde (MDA) in liver tissue homogenate. Result: the result showed that ABTS free radical scavenging activity of ethanol extract (IC50=29.26±0.49 µg/mL) was stronger than that of water extract (IC50=42.09±2.44 µg/mL), but they were lower than that of BHT as positive control (IC50=2.47±0.09 µg/mL). The ferric reducing antioxidant power of ethanol extract (FRAP=329.03±46.30 µmol/g) was higher than that of water extract (FRAP=206.03±54.30 µmol/g); they were lower than that of BHT (FRAP=1541.87±9.70 µmol/g). Water extract and ethanol extract could significantly reduce GOT activity (P<0.001) and GPT activity (P<0.001) in serum, reduce significantly the content of MDA (P<0.001) and significantly increase SOD activity (P<0.001) in the mice liver tissue homogenate. Conclusion: Compound lobelia had a certain antioxidant and satisfied hepatoprotective effects. Moreover, the liver-protective effect was concerned with antioxidant activity and enhances the body immunity. Compound lobelia is expected to be a new medicine for protecting liver.